Peningkatan Pengetahuan Status Gizi pada Remaja Putri dalam Mencegah Kejadian Anemia di SMPN 1 Conggeang: Increase Knowledge of Nutrition Status on Women Adolesence to Prevent Anemia Cases at SMPN 1 Conggeang - Emi Lindayani; Dedah Ningrum; Diding Kelana Setiadi; Reni Nuryani; Amanda Puspanditaning Sejati; Nunung Siti Sukaesih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The cases of anemia in adolescent women in Indonesia are still relatively high. There was an increase in the prevalence of anemia from 2013 to 2018 among the 15-24 year age group, from 18.4% to 32% or 14.7 million people. Anemia or low Hb levels caused by a lack of nutrients is characterized by a disturbance in hemoglobin synthesis due to a lack of nutrients that play a role in the formation of hemoglobin either due to lack of iron consumption or impaired absorption. The data on the children's health report from the Sumedang Health Office shows that adolescent women in Conggeang Junior High School are the second largest out of 29 sub-districts in the Sumedang area who are at risk of anemia, which is 58 people. The purpose of this community service is to increase the knowledge and understanding of students of Conggeang 1 Junior High School about anemia so that it can prevent anemia and, ultimately, the growth and development of children. The method used is to provide health education about anemia, iron-containing nutrition, and about blood-added tablets. The result of this community service is an increase in knowledge of the pre-test scores of participants in the implementation of health education by 48%, while the post-test scores of as much as 90.28%.